(untitled) (INNOVATIVE ECONOMY, 2025)
Semaniuk V.Z., Papinko A.I., Vitruk M.O., Drozhak V.O. E-LOGISTICS AS A DRIVER OF ADAPTABILITY AND PERFORMANCE IN SUPPLY CHAINS Purpose. The aim of the article is to substantiate the theoretical foundations and systematize the mechanisms by which e-logistics, as a component of the digital transformation of business processes, ensures the flexibility, efficiency, and sustainability of supply chains in the conditions of the global electronic economy. Methodology of research. Systemic and process approaches were used to analyse the structure of e-logistics as an integrated digital ecosystem. The study used a set of theoretical and analytical methods that ensured a systemic understanding of e-logistics transformations and the formation of an integrated concept of digital supply chain architecture. A systematic approach was used to analyse e-logistics as a coordinated ecosystem of digital processes. Structural and logical analysis was used to build a model of “four dimensions of process implementation” and systematize the elements of digital logistics. Comparative analysis made it possible to compare traditional logistics systems with new-generation digital ecosystems. A descriptive-analytical method was used to characterize digital platforms and electronic document management, which made it possible to generalize modern e-logistics practices. To identify the interrelationships between the elements of digital logistics, a model of “four dimensions of process implementation” was developed, which allows for a comprehensive assessment of the information, communication, transactional, and supply aspects of supply chain functioning. Findings. The research demonstrates that digital transformation fundamentally changes the conceptual nature of logistics — from a linear to a network-based model grounded in the interaction of autonomous digital components. The synergy between electronic document management and automated communication improves decision-making speed, reduces transaction costs, and increases the flexibility of logistics processes. The developed “four-dimensional process implementation model” illustrates how the integration of informational and physical flows forms an adaptive architecture of digital logistics. The proposed concept of document autonomy, based on blockchain and smart contract technologies, represents a new stage in e-logistics development and serves as a foundation for creating strategic, self-regulating supply chain networks. Originality. The research improves the theoretical and methodological framework of e-logistics as a systemic determinant of supply chain adaptability. It introduces, for the first time, an integrated model of digital logistics combining four dimensions of process realization, as well as a concept of autonomous documents as a foundation for building self-organizing strategic networks. Practical value. The findings can be applied by enterprises to optimize logistics processes through the digitalization of document flow, communication, and operational management. The implementation of autonomous information services enhances coordination efficiency, reduces costs, and ensures the stability of supply chain operations under conditions of global market turbulence. Key words: e-logistics, logistics costs, digital transformation, supply chains, flexibility, autonomous documents, blockchain, smart contracts, strategic networks.